PENGARUH DEBT TO ASSET RATIO DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Prabandari, Hanna Andrea Era; Maulana, Jaka; Rohyana, Cahyat (Jurnal Ilmu Akuntansi, 2023)
Changes in stock prices are one of the most important phenomena in financial markets. Every company has a goal to get a favorable share price, especially food and beverages sub-sector companies listed on the Indonesia Stock Exchange. This Final Project research aims to analyze changes in stock prices using debt to asset ratio and earning pershare analysis in food and beverages sub-sector companies. This research is a quantitative research type research. Debt to asset ratio and earning pershare as independent variables and stock price is the dependent variable. The sampling technique used in this study is purposive sampling technique, with the sample obtained being as many as 66 financial statements data of food and beverages sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. Data analysis techniques were carried out using the Data Normality Test, Product Moment Correlation, Multiple Correlation Analysis, Multiple Linear Regression Analysis, Coefficient of Determination, t Test, and F Test. The result of the t-test, a test conducted using IBM Statistic SPPS version 25, showed that the debt to asset ratio partially had no influence on stock prices and earnings pershare partially had a positive and significant effect on stock prices. The results of the F test show that the debt to asset ratio and earning pershare simultaneously have a significant effect on the stock price